Answer:
1. y = 3x - 5
2. y = -4x + 2
3. y = -3x - 4
4. y = -3x - 6
Explanation:
These questions are pretty easy. The only thing you have to do, to turn the equation into slope intercept form, is to solve for y in each equation
All the equations are in standard form, and we need to rewrite them in slope intercept form, so here are the steps
For the first equation: -3y + 9x = 15
We solve for y in the equation
-3y + 9x = 15
1. Subtract 9x from each side to isolate y
-3y + 9x - 9x = 15 - 9x
2. Simplify
-3y = 15 - 9x
3. Divide each term by -3 to get y by itself.
-3y/-3 = 15/-3 -9x/-3
4. Simplify
y = 3x - 5
For the second equation, we do the same proces, we just solve for y
−4x − y + 2 = 0
Step 1: Add 4x to both sides.
−4x − y + 2 + 4x = 0 + 4x
−y + 2 = 4x
Step 2: Subtract 2 to both sides.
−y + 2 − 2 = 4x − 2
−y = 4x − 2
Step 3: Divide both sides by -1
-y/-1 = 4x/-1 -2/-1
y = -4x + 2
For the third equation, we do the same thing too
2y + 6x = -8
Step 1: Subtract 6x to both sides.
6x + 2y − 6x = −8 − 6x
Switch -8 and -6x
2y = −6x − 8
Step 2: Divide both sides by 2.
2y/2 = -6x/2 -8/2
y = -3x - 4
And for the last equation, we do the same thing we did in the second equation
-6 - 3x - y = 0
Step 1: Add 3x to both sides.
−3x − y − 6 + 3x = 0 + 3x
−y − 6 = 3x
Step 2: Add 6 to both sides.
−y − 6 + 6 = 3x + 6
−y = 3x + 6
Step 3: Divide both sides by -1.
-y/-1 = 3x/-1 + 6/-1
y = -3x - 6